Intersubjectivity : the fabric of social becoming - Crossley, Nick, 1968- (Philosophy & social criticism (London, England), 1996)
This critical discussion of intersubjectivity as an interdisciplinary subject sheds light on our understanding of selfhood, communication, citizenship, power and community. It traces the contributions of key thinking like Buber & Husserl.